Method Development and Validation for Determination of Febuxostat from Spiked Human Plasma Using RP-HPLC with UV Detection. (27th November 2014) - Gide, Monita; Sharma, Pankaj; Saudagar, Ravindra; Shrivastava, Birendra
Abstract : A rapid, simple, selective, and specific reverse phase high performance liquid chromatography (RP-HPLC) method with UV detection (315 nm) was developed and validated for estimation of febuxostat from spiked human plasma. The analyte and internal standard (diclofenac) were extracted using LLE with diethyl ether. The chromatographic separation was performed on Shodex C-18-4E (5  μ m;250 × 4.6  mm) with a mobile phase comprised of methanol : acetate buffer pH 4, 20 mM (90 : 10 v/v), at a flow rate of 1 mL/min. Febuxostat was well resolved from plasma constituents and internal standard. The calibration curve was linear in the range of 250–8000 ng/mL. The heteroscedasticity was minimized by using weighted least square regression with weighing factor of1 / x . The intraday and interday %RSD was less than 15. Results of recovery studies prove the extraction efficiency. Stability data indicated that febuxostat was stable in plasma after three freeze thaw cycles and upon storage at −20°C for 30 days.